Using Web Blog for EFL Students in Writing Class - Hengki Kris Sanjaya; Eka Apriani; Sarwo Edy (Universitas Bengkulu, 2020)
In teaching writing, media is an essential aspect This research discovers students’ perception on weblogs as an educational tool in writing class in order to improving students’ writing skill. This quantitative research discussed 30 English Foreign Language (EFL) students. In obtaining the data, the thirty students of 8th semester at English Study Program of IAIN Curup were given a set of questionnaire to get students’ response on weblogs. After obtaining the data, the researcher analyzes the students response by counting its frequency and percentage. The findings of this research Indicated that the majority of students have positive perception on weblogs based on five indicators that is provided by researcher, those are: students confidence to write, writing skill improvement, Information and Communication Technology experience and knowledge, critical thinking promotion and accessible aspect. This research revealed that students give positive response to the use of weblogs as a medium in writing class. Furthermore, students also prefer to do their assignment on blog rather than write conventionally on paper. Findings of this research also advise the English teacher and lecturer to consider weblogs as medium and learning tool in school and university since it can encourage students’ writing achievement. The researcher also provide conclusion in this article.